Parenting Empires : Class, Whiteness, and the Moral Economy of Privilege in Latin America - Ramos-Zayas, Ana Y. (Book collections on Project MUSE., 2020)
"PARENTING EMPIRES is a comparative ethnography of wealthy white parents in two Latin American residential neighborhoods -- Ipanema, in Rio de Janeiro, Brazil; and El Condado, in San Juan, Puerto Rico -- located within two of the world's most unequal 'nations.' Although on the surface elite parents in these neighborhoods appear to be concerned with cultivating a multicultural cosmopolitanism, Ana Ramos-Zayas reveals how their parenting strategies, which employ spirituality, therapeutic language, and emphasize emotional intelligence and equality, allow them to preserve their white privilege. She defines this moral economy that maintains class and racial inequality by promoting psycho-social development as 'sovereign parenting.' In this way, Ramos-Zayas sheds light on the diverse layers of power and influence that elites hold in the Global South and how they ultimately remain complicit with rather than challenge broader nation-state projects that sustain racial hierarchies. After an introduction which charts the book's conceptual frameworks, chapters 2 and 3 explore the history, built environment, and political economy of both Ipanema and El Condado. For each of the two neighborhoods, Ramos-Zayas identifies places where parents come together across ethnoracial, class, and regional lines-what she calls 'child-centered nodules of urbanism.' Chapters 4 and 5 examine interiority capital, or the cultivation of psychological depth, emotional vocabularies, and spiritual formations among the elite and their parenting strategies. The final three chapters reveal how sovereign parenting fosters a moral framework for wealth in a context of extreme inequity. Through this framework, elites position themselves in relation to ethno-racial and regional Others, while also translating neoliberal state politics into austerity subjectivities. This book will be of interest to students and scholars in sociology, urban studies, critical ethnic studies, and Latin American studies"--